Problems of improvement of use of tax benefits mechanism (Journal of Economic Research & Business Administration, 2016)
Role of tax instruments, including tax benefits, are substantiated and widely considered in economic literature by foreign and native scholars. In despite of this, issues of creating effective system of tax benefits, contributory to forming flexible tax policy, regulated via tax mechanism instruments, is still actual. In Kazakhstan, and in other countries of CIS effective stimulation system of tax benefits hasn’t been created as yet. Tax benefits are still the element of tax stimulation of economic entities and population, and are presented mostly as a mechanism of tax base or tax rates reduce. There is no methodic of tax benefits efficiency defining.This article is devoted to research of the issues of effective tax benefits system development, which will contribute to flexible tax policy forming, regulating by the instruments of tax mechanism.
Keywords: tax benefits; tax benefits efFectiveness evaluation; tax system; small and medium business stimulation